2006
DOI: 10.5344/ajev.2006.57.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine Rooting Patterns: A Comprehensive Analysis and a Review

Abstract: now deceased. We thank Anna Vu and Christine Stockert for technical assistance. David M. Eissenstat, Kerri L. Steenwerth, and M. Andrew Walker made many helpful comments that greatly improved both the scope and clarity of this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(28 citation statements)
references
References 17 publications
(17 reference statements)
0
21
0
5
Order By: Relevance
“…However, given the complex interactions between the rootstock, cultivar, and environment, local long-term studies are necessary before a specifc type of rootstock can be recommended for a specifc edaphoclimatic condition (Marín et al 2021). Tis implies that the results obtained for a particular cultivarrootstock combination in a specifc environment cannot be widely extrapolated to other situations [22,23]. In this context, these specifcities may explain the contradictory results obtained in previous studies.…”
Section: )mentioning
confidence: 95%
See 1 more Smart Citation
“…However, given the complex interactions between the rootstock, cultivar, and environment, local long-term studies are necessary before a specifc type of rootstock can be recommended for a specifc edaphoclimatic condition (Marín et al 2021). Tis implies that the results obtained for a particular cultivarrootstock combination in a specifc environment cannot be widely extrapolated to other situations [22,23]. In this context, these specifcities may explain the contradictory results obtained in previous studies.…”
Section: )mentioning
confidence: 95%
“…Indeed, several factors contribute to the drought response of the rootstock, including root anatomy, growth patterns, and chemical and physical signals related to stomatal regulation. Smart et al [22] found that diferences in the proportion of roots in the diferent soil layers, rather than diferences in the ability of rootstocks to develop roots at depth, conferred high-vigour rootstocks with improved access to water and minerals from the deeper soil profle. Tus, it is likely that a combination of all of these factors contribute to the drought response when a rootstock is subjected to drought conditions.…”
Section: Rootstocks Infuence Water Uptake and Leaf Gasmentioning
confidence: 99%
“…La fijación de la planta al suelo y el soporte estructural es una de ellas, aunque la existencia de zarcillos en la vid limita la necesidad de las raíces como soporte estructural (Smart et al 2004). De este modo, la evolución de la forma y la función del sistema radical de las viñas está relacionado directamente con otras funciones más importantes como la absorción de agua y de nutrientes (Smart et al 2004), la acumulación de sustancias de reserva o la síntesis de diversos compuestos orgánicos (Richards 1983;Morlat et al 1993a). Aunque todo el sistema radical de la planta realiza estas funciones, algunas partes están más especializadas que otras dependiendo de la edad y tamaño de las mismas.…”
Section: Infiltración Y Disponibilidad Hídrica Del Suelounclassified
“…La variedad o la especie afectan a la distribución radical, ya que las propiedades genéticas definen características como el ángulo de enraizamiento (geotropismo), o la longitud y grosor de las raíces (Bouard 1971;Reynier 1995). Sin embargo, algunos autores sostienen que estas diferencias tiene pocos efectos en la distribución del sistema radical adulto (Champagnol 1984), y que las propiedades genéticas del patrón pueden definir la densidad radical, pero que son los factores ambientales del suelo los que explican la distribución del sistema radical (Southey et al 1988;Smart et al 2004).…”
Section: Desarrollo Radical a Lo Largo Del Ciclounclassified
See 1 more Smart Citation